1995
DOI: 10.1159/000179076
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Erythropoietin Inhibits the Cutaneous Vasodilatation Induced by Acetylcholine

Abstract: We investigated by means of telethermography the contractile response of cutaneous vessels to recombinant erythropoietin (rHuEPO) and the effects of this hormone on the vasodilatation induced by either acetylcholine, which is endothelium-dependent, and nitroprusside, which is endothelium-indepen-dent. Experiments were carried out in 12 healthy volunteers. Graded doses of rHuEPO (25, 50, 500U/min), acetylcholine (7.5 and 15µg/min), sodium nitroprusside (3 and 10 µg/min), and saline solution (sodium chloride 0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
0
12
1
Order By: Relevance
“…Additionally, a reduced effect of a selective NOS inhibitor (N G -nitro-L-arginine methyl ester; L-NAME) on acetylcholine-induced vasodilatation was observed in the Epo group, indicating that NOS activity had been inhibited or sensitivity of NOS to L-NAME was decreased in Epo-treated rabbits (180). Similar effects have been observed in healthy human cutaneous vessels, in which local infusion of high doses of Epo could revert endothelium-dependent vasodilatation induced by acetylcholine (22). Taken together, there are several indications that Epo can enhance and diminish NO release, which may depend on concentrations and perhaps the presence of high blood pressure or a uremic environment.…”
Section: How Does Epo Influence the Cardiorenal Connectors?mentioning
confidence: 61%
“…Additionally, a reduced effect of a selective NOS inhibitor (N G -nitro-L-arginine methyl ester; L-NAME) on acetylcholine-induced vasodilatation was observed in the Epo group, indicating that NOS activity had been inhibited or sensitivity of NOS to L-NAME was decreased in Epo-treated rabbits (180). Similar effects have been observed in healthy human cutaneous vessels, in which local infusion of high doses of Epo could revert endothelium-dependent vasodilatation induced by acetylcholine (22). Taken together, there are several indications that Epo can enhance and diminish NO release, which may depend on concentrations and perhaps the presence of high blood pressure or a uremic environment.…”
Section: How Does Epo Influence the Cardiorenal Connectors?mentioning
confidence: 61%
“…22,23 Infusion of EPO into the lower limbs of healthy volunteers suggested that EPO may impair synthesis of endothelial NO resulting in vasoconstriction. 24 Incubation with EPO of human coronary artery endothelial cells to 24 hours inhibited NO production and endothelial nitric oxide synthase (eNOS) expression while stimulating DNA synthesis. 25 However, short-term EPO stimulation of vascular endothelial cells in culture generally has not shown modification of NO synthesis or regulation of expression of endothelin-1 or nitric oxide synthase, data interpreted as suggesting that the hypertensive effect of EPO is not a direct effect on endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Using telethermography, it has been demonstrated that the acetylcholine-induced relaxation of the dorsal pedal subcutaneous artery of normal humans was blunted by graded doses of EPO [6], suggesting that EPO may impair the synthesis of endothelial NO in this vasculature. Moreover, EPO treatment (150 units:kg −" ; twice per week for 6 weeks) in rats raised the blood pressure and impaired the hypotensive response to sodium nitroprusside, a NO donor, but did not change caudal artery contraction in response to depolarization induced by 68 mM potassium [7], suggesting that EPO-induced hypertension may be associated with an impaired vasodilatory response to NO.…”
Section: Introductionmentioning
confidence: 99%